Assessing The Socio-Economic Characteristics of Higher Education Subsidies’ Beneficiaries in Egypt. Problem of Subsidizing the Rich - El-Gerby, Sarah (AUC Knowledge Fountain, 2012)
This thesis explores the socioeconomic characteristics which influence the decision of joining HE in Egyt. it assesses the characteristics of the beneficiaries, and identifies the socioeconomic characteristics of students of private vs. free public universities in Egypt. It examines the socioeconomic correlates of joining higher education in Egypt; and among university students the correlates of the choice between joining public versus private university. It uses probit and logit models adjusted for self-selection bias. The study focuses on three key variables to assess equity issues: gender, wealth, and urban/rural/slum residence. Results show that the socioeconomic background of students’ families is highly correlated with university attendance. The main determinants for joining university are wealth, high school score, and type of secondary school attended. The staggering finding is that socio-economic characteristics fail to differentiate between those who attend tuition-free public and those who attend private HE institutions that charge high fees.